Time Spent on Dedicated Patient Care and Documentation Tasks Before and After the Introduction of a Structured and Standardized Electronic Health Record - Joukes, Erik; Abu-Hanna, Ameen; Cornet, Ronald; de Keizer, Nicolette F. (Applied Clinical Informatics, 2018)
Background Physicians spend around 35% of their time documenting patient data. They are concerned that adopting a structured and standardized electronic health record (EHR) will lead to more time documenting and less time for patient care, especially during consultations.Objective This study measures the effect of the introduction of a structured and standardized EHR on documentation time and time for dedicated patient care during outpatient consultations.Methods We measured physicians' time spent on four task categories during outpatient consultations: documentation, patient care, peer communication, and other activities. Physicians covered various specialties from two university hospitals that jointly implemented a structured and standardized EHR. Preimplementation, one hospital used a legacy-EHR, and one primarily paper-based records. The same physicians were observed 2 to 6 months before and 6 to 8 months after implementation.We analyzed consultation duration, and percentage of time spent on each task category. Differences in time distribution before and after implementation were tested using multilevel linear regression.Results We observed 24 physicians (162 hours, 439 consultations). We found no significant difference in consultation duration or number of consultations per hour. In the legacy-EHR center, we found the implementation associated with a significant decrease in time spent on dedicated patient care (−8.5%). In contrast, in the previously paper-based center, we found a significant increase in dedicated time spent on documentation (8.3%) and decrease in time on combined patient care and documentation (−4.6%). The effect on dedicated documentation time significantly differed between centers.Conclusion Implementation of a structured and standardized EHR was associated with 8.5% decrease in time for dedicated patient care during consultations in one center and 8.3% increase in dedicated documentation time in another center. These results are in line with physicians' concerns that the introduction of a structured and standardized EHR might lead to more documentation burden and less time for dedicated patient care.
Keywords: electronic health record; implementation; healthcare professionals; patient care; documentation time